2019
DOI: 10.1155/2019/5038153
|View full text |Cite
|
Sign up to set email alerts
|

Capacity ofHistoplasma capsulatumto Survive the Composting Process

Abstract: Histoplasma capsulatum (H. capsulatum) is a thermal-dimorphic fungus, the causal agent of histoplasmosis. Its presence in the environment is related with chicken manure due to their high nitrogen and phosphorus content. In Colombia, chicken manure is the most used raw material in the composting process; however, there is no information about the capacity of H. capsulatum to survive and remain viable in a composted organic fertilizer. To address this question, this study shows three assays based on microbiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Our previous studies demonstrated that properly performed composting can decrease the amount of detectable H. capsulatum in organic fertilizers. 19 Several factors may explain the observed high proportion of positive samples among composted fertilizers in this study. First, it is possible that the highly sensitive 100-kDa real-time PCR assay detects DNA from nonviable fungus, and the positive signal indicates the history of H. capsulatum contamination in the composted fertilizers.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Our previous studies demonstrated that properly performed composting can decrease the amount of detectable H. capsulatum in organic fertilizers. 19 Several factors may explain the observed high proportion of positive samples among composted fertilizers in this study. First, it is possible that the highly sensitive 100-kDa real-time PCR assay detects DNA from nonviable fungus, and the positive signal indicates the history of H. capsulatum contamination in the composted fertilizers.…”
Section: Discussionmentioning
confidence: 75%
“…We evaluated the performances of 100-kDa real-time and Hc100 nested PCR for the detection of H. capsulatum DNA in environmental samples and used these assays to investigate the presence of this fungus in these substrates in Colombia. Our results demonstrated that although both assays considerably outperformed culture, which was only able to detect H. capsulatum in a single sample, 18,19 100-kDa real-time PCR was able to identify 600% more positive samples compared with the Hc100 nested PCR assay. The higher sensitivity of real-time PCR compared with nested PCR was not surprising, given that the real-time PCR assay did not rely on visualization of PCR products on the agarose gel, and therefore, lower concentrations of PCR products could be detected with this method.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In agreement with our observation other authors documented that temperature up 29°C and humidity of 67–87% are favorable for the survival of the mycelial form of the fungus. Rainfall and or humidity can cause maceration of the skin which can easily be traumatized and allow entrance of the fungus into the body of horses ( 18 ). Here a higher humidity but a lower rainfall was associated with an increased risk of epizootic lymphangitis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Histoplasma grows especially well in soil or other environmental material containing large amounts of bird or bat droppings, although this is not a requirement for its presence in the environment. Histoplasma has been detected in some organic fertilizers in Latin America, but more studies are needed to understand whether the fungus can survive commercial fertilizer manufacturing processes [ 23 , 24 ].…”
Section: Histoplasma In the Environmentmentioning
confidence: 99%